ELDERLY PATIENT WITH CHRONIC HEART FAILURE IN THE GENERAL PRACTICE - V.V. Zhdan; O.Ye. Kitura; Ye.M. Kitura; M.Yu. Babanina; V.G. Volchenko; M.V. Tkachenko (Проблеми екології та медицини)
The paper elucidates the peculiarities of heart failure course in elderly patients, as well as issues of pharmacotherapy, chronic heart failure. Features of the pathogenetic therapy of ß-blockers and ACE inhibitors, as well as diuretics and cardiac glycosides have been considered.